Maritime Diplomacy in Realizing the Vision of Golden Indonesia 2045 through the Concept of World Maritime Axis - Dao, Yunias (Indonesian Scientific Publication, 2024)
Indonesia plays an important role in global maritime dynamics. The maritime sector is critical to international trade and regional security. The concept of the World Maritime Axis has been introduced as the basis for Indonesia's maritime development. The Golden Indonesia Vision 2045 is Indonesia's long-term roadmap to become a major economic power. It focuses on the optimal use of the maritime sector, with maritime diplomacy playing an important role in achieving this vision. This article examines the research objectives to answer the main question: